Novel Possible Protein Targets in Neovascular Age-Related Macular Degeneration: A Pilot Study Experiment - Coronado, Bruno Nobre Lins; da Cunha, Felipe Bruno Santos; de Oliveira, Raphaela Menezes; Nóbrega, Otávio de Toledo; Ricart, Carlos André Ornelas; Fontes, Wagner; de Sousa, Marcelo Valle; de Ávila, Marcos Pereira; Martins, Aline Maria Araújo (Frontiers in Medicine, 2022)
Age-related macular degeneration (AMD) is among the world's leading causes of blindness. In its neovascular form (nAMD), around 25% of patients presents further anatomical and visual deterioration due to persistence of neovascular activity, despite gold standard treatment protocols using intravitreal anti-VEGF medications. Thus, to comprehend the molecular pathways that drive choroidal neoangiogenesis, associated to the vascular endothelial growth factor (VEGF) is an important step to elucidate the mechanistic events underneath the disease development. This is a pilot study, a prospective, translational experiment, in a real-life context aiming to evaluate the protein profiles of the aqueous humor of 15 patients divided into three groups: group 1, composed of patients with nAMD, who demonstrated a good response to anti-VEGF intravitreal injections during follow-up (good responsive); group 2, composed of patients with anti-VEGF-resistant nAMD, who demonstrated choroidal neovascularization activity during follow-up (poor/non-responsive); and group 3, composed of control patients without systemic diseases or signs of retinopathy. For proteomic characterization of the groups, mass spectrometry (label-free LC-MS/MS) was used. A total of 2336 proteins were identified, of which 185 were distinctly regulated and allowed the differentiation of the clinical conditions analyzed. Among those, 39 proteins, including some novel ones, were analyzed as potential disease effectors through their pathophysiological implications in lipid metabolism, oxidative stress, complement system, inflammatory pathways, and angiogenesis. So this study suggests the participation of other promising biomarkers in neovascular AMD, in addition to the known VEGF.